Implementing Numeracy Across-Curriculum : An Adaptation of Australian Approaches in Indonesia’s Merdeka Curriculum - Rosita, Hana; Wiryanto, Wiryanto; Mariana, Neni (Jurnal Paedagogy, 2025)
This study aims to explore numeracy across-curriculum instruction in Australia that can be adapted to Merdeka Curriculum to serve as learning resources for teachers. Using a systematic literature review method, the research addresses four key questions related to the definition, implementation, educator understanding, and adaptability of cross-curricular numeracy. Literature was selected using strict inclusion criteria, focusing on recent studies discussing numeracy in the context of primary education in Australia and Indonesia. The analysis of eight selected articles reveals two exemplary activities that can be adapted: CUPS and Body Percussion. CUPS (Cross-Curricular Unit on Portion Size) can be implemented in Physical Education (PJOK) Phase B in the topic of Nutritious and Balanced Eating Patterns to instill concepts of numbers and measurement concepts. Body Percussion can be implemented in Arts (SBdP) Phase B on Rhythmic Music Patterns using body percussion to instill number concept.